PENGARUH PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PT. BANK MESTIKA DHARMA, Tbk - Robin Robin; Tini (JEBS (Journal of Economic and Business Student), 2023)
This research was conducted because there was a phenomenon where there were complaints about the slow service to customers.  The purpose of this study was to determine the effect of training and human resource development on employee performance at PT.  Bank Mestika Dharma, Tbk.  On the results of other studies and the opinion of experts who state that training and development of Human Resources can improve employee performance.  This study is a quantitative study with a population of 320 people and a sample of 76 respondents, using the Simple Random Sampling technique.  The results of the study by conducting a t-test on the training variable (X1) obtained the tcount value of 6.914 > ttable 1.993 and the human resource development variable (X2) with the results tcount7.866 > ttable1.993 both variables at a significant level of 0.000 > 0.05 so that it can be concluded that the variable Human resource training and development has a positive and significant effect on employee performance.  An f-test was performed with fcount 108.217 > ftable 3.12 at a significant level of 0.000 > 0.05 with the conclusion that training and human resource development simultaneously affect employee performance.  Based on the determinant test of the coefficient R2 with a result of 0.748, which means that training and human resource development have an effect of 74.8% on employee performance at PT.  Bank Mestika Dharma, Tbk.